A cell free biomembrane platform for multimodal study of influenza virus hemagglutinin and for evaluation of entry-inhibitors against hemagglutinin - Roy, Arpita; Byrne, Sylvester; Sarangi, Nirod Kumar; Murphy, Paul V.; Keyes, Tia E. (Frontiers in Molecular Biosciences, 2022)
Seasonal periodic pandemics and epidemics caused by Influenza A viruses (IAVs) are associated with high morbidity and mortality worldwide. They are frequent and unpredictable in severity so there is a need for biophysical platforms that can be used to provide both mechanistic insights into influenza virulence and its potential treatment by anti-IAV agents. Host membrane viral association through the glycoprotein hemagglutinin (HA) of IAVs is one of the primary steps in infection. HA is thus a potential target for drug discovery and development against influenza. Deconvolution of the multivalent interactions of HA at the interfaces of the host cell membrane can help unravel therapeutic targets. In this contribution, we reported the effect of a multivalent HA glycoprotein association on various glycosphingolipid receptors (GD1a, GM3, GM1) doped asymmetrically into an artificial host membrane spanned across an aqueous filled microcavity array. The extent of HA association and its impact on membrane resistance, capacitance, and diffusivity was measured using highly sensitive electrochemical impedance spectroscopy (EIS) and fluorescence lifetime correlation spectroscopy (FLCS). Furthermore, we investigated the inhibition of the influenza HA glycoprotein association with the host mimetic surface by natural and synthetic sialic acid-based inhibitors (sialic acid, Siaα2,3-GalOMe, FB127, 3-sialyl lactose) using electrochemical impedance spectroscopy and observe that while all inhibit, they do not prevent host binding. Overall, the work demonstrates the platform provides a label-free screening platform for the biophysical evaluation of new inhibitors in the development of potential therapeutics for IAV infection prevention and treatment.